2017
DOI: 10.1161/atvbaha.117.309751
|View full text |Cite
|
Sign up to set email alerts
|

Class III PI3K Positively Regulates Platelet Activation and Thrombosis via PI(3)P-Directed Function of NADPH Oxidase

Abstract: Platelet VPS34 is critical for thrombosis but dispensable for hemostasis. VPS34 regulates platelet activation by influencing NOX assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 48 publications
4
67
0
1
Order By: Relevance
“…With the importance of NOXs in platelet function emerging and their regulation mechanism unveiling, such as suggested by the study of Delaney et al 2 and ours, 1 we agree with the authors that it is imperative for future studies to further reveal the regulation network involving NOX isoforms and VPS34 in the context of platelet activation and thrombosis.…”
Section: In Responsesupporting
confidence: 84%
See 2 more Smart Citations
“…With the importance of NOXs in platelet function emerging and their regulation mechanism unveiling, such as suggested by the study of Delaney et al 2 and ours, 1 we agree with the authors that it is imperative for future studies to further reveal the regulation network involving NOX isoforms and VPS34 in the context of platelet activation and thrombosis.…”
Section: In Responsesupporting
confidence: 84%
“…Nevertheless, both our study 1 and the study conducted by Delaney et al 2 demonstrate that low dose agonists (thrombin, 0.018 U/mL and 0.025 U/mL; collagen, 0.5 μg/mL; or CRP, 0.5 μg/mL) still activate significant ROS generation in platelets deficiency of NOX1, NOX2, or VPS34, suggesting the existence of other mechanisms of ROS generation independent of these proteins. The NOX family consists of 7 catalytic homologues, 7,8 in addition to NOX1 and NOX2, NOX4 is also detected in platelets.…”
Section: In Responsesupporting
confidence: 43%
See 1 more Smart Citation
“…Furthermore, a subsequent study confirmed that 3-MA suppresses autophagy by inhibiting class III PI3K [58]. The inhibitor of class III PI3K 3-MA blocks the plasma membrane translocation of important cytoplasmic subunits of NOX2 NADPH oxidase, further affecting the assembly and activation of NOX2 complex on the platelet membrane and subsequently reducing ROS production, ultimately affecting platelet activation and thrombosis [59]. Furthermore, the NOX2 NADPH was identified as one of the key sources of ROS, and a recent study has revealed a novel role for the NOX2 NADPH oxidase in the activation of autophagy [60].…”
Section: Ohmentioning
confidence: 82%
“…This mechanism is in concert with the role of platelet ROS in thrombus formation: platelet-specific deficiency of class III phosphoinositide 3-kinase (also known as vacuolar protein sorting 34) attenuates thrombosis via influencing nicotinamide adenine dinuclectide phosphate oxidases assembly. 59 Given the complexity of ROS signals, how to therapeutically modulate the levels of endothelial ROS to curtail thrombosis warrants further study. Interestingly, in a randomized, placebo controlled clinical trial in patients with antiphospholipid syndrome, treatment with ubiquinol, the reduced equivalent of coenzyme Q10, improved endothelial function and reduced thrombotic risk markers, likely through reduced EC inflammation related to oxidative stress.…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%